Beyond technology: A research agenda for social sciences and humanities research on renewable energy in Europe - Krupnik, S.; Wagner, A.; Koretskaya, O.; Rudek, T. J.; Wade, R.; Mišík, M.; Akerboom, S.; Foulds, C.; Stegen, K. S.; Adem, C.; Batel, S.; Rabitz, F.; et al. (Energy Research and Social Science, 2022)
This article enriches the existing literature on the importance and role of the social sciences and humanities (SSH) in renewable energy sources research by providing a novel approach to instigating the future research agenda in this field. Employing a series of in-depth interviews, deliberative focus group workshops and a systematic horizon scanning process, which utilised the expert knowledge of 85 researchers from the field with diverse disciplinary backgrounds and expertise, the paper develops a set of 100 priority questions for future research within SSH scholarship on renewable energy sources. These questions were aggregated into four main directions: (i) deep transformations and connections to the broader economic system (i.e. radical ways of (re)arranging socio-technical, political and economic relations), (ii) cultural and geographical diversity (i.e. contextual cultural, historical, political and socio-economic factors influencing citizen support for energy transitions), (iii) complexifying energy governance (i.e. understanding energy systems from a systems dynamics perspective) and (iv) shifting from instrumental acceptance to value-based objectives (i.e. public support for energy transitions as a normative notion linked to trust-building and citizen engagement). While this agenda is not intended to be—and cannot be—exhaustive or exclusive, we argue that it advances the understanding of SSH research on renewable energy sources and may have important value in the prioritisation of SSH themes needed to enrich dialogues between policymakers, funding institutions and researchers. SSH scholarship should not be treated as instrumental to other research on renewable energy but as intrinsic and of the same hierarchical importance.